ANALYSIS OF THE IMPACT OF EDUCATION COSTS ON SCHOOL SELECTION DECISIONS AT VOCATIONAL HIGH SCHOOL DEPARTMENTS IN THE GREATER BANDUNG METROPOLITAN AREA - Yusnaini, Yusnaini; Iskandar, Fatimah Nurjannati (Journal of Social and Economics Research, 2025)
This study aims to analyze the impact of education costs on the decision to become a student at a Vocational High School (SMK) majoring in Visual Communication Design (DKV) in the Greater Bandung Metropolitan area. The background of this study shows an imbalance between the increasing number of SMKs and the number of students, especially in the DKV department which actually experiences a low participation rate. People tend to be reluctant to choose SMK DKV because of the perception that the high cost of education is not commensurate with the benefits obtained, such as job prospects after graduation. This study uses a quantitative approach with a survey method of the entire population of SMK DKV students in the area, totaling 191 people. The results of the analysis show that education costs have a positive and significant influence on the decision to become a student, both partially and simultaneously with other variables such as the quality of educational services, institutional image, and social media marketing. Education costs are proven to be one of the main considerations in the process of evaluating alternative schools and decision-making by prospective students. These findings reinforce the importance of transparency and education cost policies that are balanced with the value of benefits in order to increase public interest in vocational education, especially in the field of visual communication design.